BPOM Certification as a Quality Signal: Its Impact on Amifa Skinglow Local Skincare Products - Rosa Sapitri; Candra Candra (JURNAL ECONOMINA, 2026)
Indonesia's local skincare industry is experiencing rapid growth through digital platforms. However, consumers continue to face information asymmetry regarding product safety and quality. This study examines the effects of BPOM certification, brand awareness, perceived quality, promotion, and customer trust on purchase intention toward the local skincare brand Amifa Skinglow. Using an explanatory quantitative research design, data were collected from 153 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate an R-square value of 0.770, demonstrating that the proposed model explains a substantial proportion of the variance in purchase intention. All independent variables have positive and significant effects on purchase intention. Customer trust emerged as the strongest predictor (β = 0.571), followed by brand awareness (β = 0.264), highlighting that consumer trust and brand reputation play a more influential role in shaping purchase intention than formal product certification.